IJRO INTIZOMINI TA’MINLASHDA RAQAMLI BOSHQARUV TIZIMLARINING ROLI - Aslanov Sarvar Tolmasovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the role of digital management systems in ensuring execution discipline within modern organizations. It analyzes the theoretical foundations of execution discipline, its distinction from labor discipline, and their interrelation in organizational management. The study highlights how digital technologies enhance transparency, efficiency, and accountability in the execution of managerial decisions. In addition, the article explores the advantages of digital management systems, including real-time monitoring, automation of document flow, and reduction of human error. It also discusses existing challenges in the implementation of such systems, such as insufficient digital skills, technical infrastructure limitations, resistance to change, and information security risks. Furthermore, the article provides an overview of international experiences in countries such as Estonia, South Korea, Singapore, and the United Kingdom. Based on the analysis, conclusions and recommendations are presented to improve execution discipline through the wider adoption of digital governance tools.